Pengembangan Video Pembelajaran Fisika Pada Materi Sistem Tata Surya Berbasis Virtual Reality Video 3600 dengan Software Blender Pada Kelas VIII SMP/MTs - Febri Iskandar; Hadiyati Idrus (Edusainstika: Jurnal Pembelajaran MIPA, 2022)
This research aims to develop a physics learning video on the solar system material based on virtual reality video 3600 with blender software for class VIII SMP/MTs, as an effort to increase student's interest and passion in learning. The research method used is Research and Development with a 4D model (define, design, develop, and disseminate). This research is only carried out until the development stage. The problem to be studied is obtained at the definition stage. Then, the virtual reality-based 3600 learning video is designed in such a way in the design stage. At the development stage, validation was carried out by 3 validators, namely 2 physics lecturers, and 1 physics teacher. After the product is declared valid, it is continued with trials on students and educators to find out its practicality. The validation of the virtual reality-based 3600 learning video that was developed obtained a percentage of 84.37%. These results show that this video is very valid. Tests on 3600 virtual reality-based learning video students showed that this product was very practical with a percentage of 83.33% by students and 82.5% by educators. So, this learning video can be used as a medium for learning Physics, especially the material for the solar system.